?POLYMETALLIC COMPLEXES Part XLIV. Complexes of Cobalt (II), Nickel (II), Copper (II), Zinc (II), Cadmium (II) and Mercury II with Doubly-Bidentate 0 N Z N 0 Donor Chelating Azo Dye Ligands, 4,4'-Bis (2'-Hydroxy-l'-Naphthyl-Azo)-Diphenyl and l,4- (Biological Sciences - PJSIR, 1995)
The title doubly-bidentate bis-azo dye ligands form dimeric complexes of the type [M2L/L'2(HP)4]' [M'2L/L'2l where M=Co(II), Ni(I1),Cu(II), M'=Zn(II), Cd(II), Hg(II). The complexes of the former category are found to be six coordinated, either octahedral or distorted octahedral and the complexes of the later type are four-coordinated with a tetrahedral geometry around the metal ions. The complexes have been characterized basing upon analytical, conduc- tance, magnetic susceptibility, i.r., electronic, T.G.A., D.T.A., E.S.R. and N.M.R. data.